IMPLIKASI PENGENAAN PAJAK PENGHASILAN FINAL TERHADAP PENGHITUNGAN PAJAK PENGHASILAN BADAN PADA PT. EMPAT TUJUH ABADI JAYA - Christian, Yuyun Apriana; Nangoi, Grace B.; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
PP 46 2013 is a regulation issued by the government to provide convenience for SMEs taxpayers. Taxpayers who apply this regulation must have gross circulation below Rp. 4.8 billion. By using this regulation, taxpayers simply multiply the gross circulation in 1 month at the final rate of 1%. The purpose of this study is to compare the income tax to be paid by using final income tax and income tax laws and to determine more efficient regulations to be implemented by PT. Empat Tujuh Abadi Jaya. The analytical method used in this study is descriptive qualitative. The results showed that the income tax of PT. Empat Tujuh Abadi Jaya based on the income tax law is Rp. 34,135,000.00, while based on the final 1% income tax is Rp. 46,694,000.00. It can be concluded that it will be more efficient for PT. Empat Tujuh Abadi Jaya to pay income tax by using income tax laws because the amount of tax to be paid is smaller.